Burnout Syndrome by assistencial work stress in groups of university teachers - Ponce Díaz, Carlos R. (2005)
Objective: To acknowledge the possible presence of the "Burnout" syndrome caused by existential work stress in university professors group of a state university who belong to different career area.To find possible significant differences in the "Burnout" syndrome caused by existential work stress in different career area and according to the variable: sex, marital status, sport practice, health and teaching condition. Design: It is descriptive, comparative, correlational and analytic preformed on university proffesors distributed in 5 carrer area, in which an effort was mad to find the presence and implication of the "Burnout" syndrome.